2010
DOI: 10.1111/j.1440-1746.2010.06238.x
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection with hepatitis C virus following sustained virological response in injection drug users

Abstract: The rate of reinfection following treatment for HCV infection among current and former IDUs engaged in a multidisciplinary program is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 15 publications
(21 reference statements)
1
53
0
Order By: Relevance
“…Although ongoing injecting drug use has been in practice a barrier for commencing an individual on treatment, if a reduced risk of reinfection after spontaneous viral clearance can be observed -and if also seen in those who have cleared infection through antiviral therapy (Backmund, Meyer, & Edlin, 2004;Dalgard, 2005;Grebely et al, 2010) -this suggests that treatment of both former and current IDUs may be viable. The likelihood of reinfection should be considered when conducting an assessment of the benefits and drawbacks of antiviral therapy of this population for HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although ongoing injecting drug use has been in practice a barrier for commencing an individual on treatment, if a reduced risk of reinfection after spontaneous viral clearance can be observed -and if also seen in those who have cleared infection through antiviral therapy (Backmund, Meyer, & Edlin, 2004;Dalgard, 2005;Grebely et al, 2010) -this suggests that treatment of both former and current IDUs may be viable. The likelihood of reinfection should be considered when conducting an assessment of the benefits and drawbacks of antiviral therapy of this population for HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of HCV reinfection following a sustained viral response (SVR) among this group remains a concern, causing reluctance among some clinicians to treat these individuals. Several studies have considered HCV reinfection among PWID following SVR [7,8,9,10,11,12] and, in a meta-analysis, Aspinall et al estimate the rate of HCV reinfection following SVR to be 2.4/100…”
Section: Introductionmentioning
confidence: 99%
“…And, P11=P44, P12=P42, P13=P43, P17=P27=P37=P47= P57=P67=μ and for k=1,…, (27, Some research has found that following spontaneous clearance of an acute infection a proportion of individuals may have protective immunity to re-infection; however, findings regarding a conferring of a protective immunity are equivocal [40][41][42][43]. In order to capture the possibility of some level of a protective immunity, a corresponding state (z) was included in the natural history model with a low transition probability (0.25) [19].…”
Section: Quasi-markov Model Transition Probabilities and Parametersmentioning
confidence: 99%